Interprofessional culinary education workshops at the University of Saskatchewan - Lieffers, Jessica; Wolfson, Erin; Sivapatham, Gabilan; Lang, Astrid; McEwen, Alexa; D'Eon, Marcel; Henry, Carol (Canadian Medical Education Journal, 2021)
Implication Statement If you want to offer your students an enjoyable and worthwhile interprofessional activity to learn about issues in community nutrition, your university can cook up these interprofessional culinary education workshops. Start with a few enthusiastic students from various health professional programs who can organize, promote, and lead. Include faculty and/or staff to support the students and apply for internal funding. Find workshop facilitators (e.g., chefs), and arrange for program evaluation. It is best to choose workshop topics and themes relevant to your local situation. Ensure workshops are structured to facilitate cooperative and experiential learning. Students will find these sessions informative, practical, and enjoyable.